HOUSING CHARACTERISTIC IN PALANGKA RAYA LESSON LEARNING FROM MITIGATION AND ADAPTATION PROGRAM - Mandarin Guntur (Jurusan Arsitektur UPR, 2014)
Lesson learning from mitigation and adaptation program on urban housing area in Palangka Raya is an advance urban housing development effort to cope extreme global climate change. This study is aimed at explaning adaptation and mitigation pattern on urban peat swamp housing area dealing with climate change according to local people approach and government approach. With comparing through mitigation pattern and adaptation pattern which have been implemented by government program and by local people on urban housing area, the level of adaptation and mitigation on urban housing area can be assessed. The result of the study shown that variability of adaptation and mitigation on certain housing area will be increasing the adaptation and mitigation of its urban region to cope global climate change.